Gender Equality in the Global Research Publication: The Bibliometric Review and Scientific Visualization - Abd. Rasyid, Syamsul Bahri (Pusat Kajian Humaniora FBS Universitas Negeri Padang, 2022)
Despite the progress over the years, there are still many challenges to achieving basic human rights, namely “gender equality”. The language of “gender equality” was mobilized by feminists as a way to incorporate women's rights into the international development agenda. Using bibliometric analysis of scientific journal articles taken from the Scopus database, which totaled 504 journal articles, this study aims to document evidence of research activities in 2012-2021 in the Scopus database, and visualize it using VOSviewer and NVivo 12 plus software. The article reports on the publication and its citation structure, key trends, and its growing push toward co-authoring. This study also visualizes the most prominent topics and authors in the form of a network, using VOSviewer's bibliometric analysis and mapping of themes and their correlations using NVivo 12 plus. The novelty of this research is the composition of limitations in the Scopus database, as well as data processing using VOSviewer and NVivo 12 plus software. Further research, it is necessary to enrich the composition of limitations in the Scopus database, and compare it with the Web of Science database.